Effect of glycerol and corn oil on physicochemical properties of polysaccharide films : a comparative study - Cerqueira, M. A. (2012)
The aim of this work was to evaluate the influence of glycerol and corn oil on physicochemical properties of polysaccharide-based films. The polysaccharides used were galactomannan from Gleditsia triacanthos and chitosan. Fourier-transform infrared spectroscopy, differential scanning calorimetry and thermogravimetric analysis were performed, together with determinations of moisture content, solubility, water vapor permeability and mechanical properties. Structure–properties relationships were established, relating the two polysaccharides’ structures with the way they interact with water, other film’s constituents (glycerol and oil) and the resulting properties. The presence of glycerol and corn oil originated a more hydrophilic structure and a decreased affinity of the film matrix to water, respectively, in both polysaccharides. However, the two polysaccharides presented different behaviors in terms of glass transition temperature, water vapor permeability and elongation-at-break that have been related with the particularities of their structure: while for the galactomannan the specific sorption sites for water are the O–H groups, for chitosan those are O–H and/or NH2 groups. The present work provides insight regarding the physicochemical properties of polysaccharide-based films and established relationships with polymers’ structure, showing that the two polysaccharides studied here have adequate properties to be used as packaging materials for specific food applications.